Perspectives on sipuleucel-T: Its role in the prostate cancer treatment paradigm - James L. Gulley; Peter Mulders; Peter Albers; Jacques Banchereau; Michel Bolla; Klaus Pantel; Thomas Powles (OncoImmunology)
Sipuleucel-T is an autologous cellular immunotherapy approved in the US for patients with asymptomatic or minimally symptomatic metastatic castration-resistant prostate cancer (mCRPC). This significant advance for mCRPC treatment provides healthcare professionals with another effective therapy to extend survival. As an immunotherapy, sipuleucel-T possesses specific characteristics differentiating it from traditional therapies. At a roundtable meeting of experts, sipuleucel-T data were discussed, focusing on interpretation and clinical implications. Important differences between immunotherapies and traditional therapies were explored, e.g., mode of action, outcomes, data consistency and robustness, timing of sipuleucel-T treatment, and future perspectives in areas such as short-term markers of long-term benefit.